Efficacy of iron proteinate fed to sows in meeting the iron needs of baby pigs - Schoneweis, D.A.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials involving 33 litters of pigs and more than 1,300 blood samples demonstrated that feeding iron proteinate (250 PPM) to the sows during the last one-third of gestation and lactation is not an effective way to supply the iron needs of baby pigs if they have limited access to the sows’ fecal material.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Iron proteinate; Sows; Gestation; Lactation